Frequency of EEG Changes In Different Types of Clinically Diagnosed Epileptic Patients - Sa, Dhali; KK, Barman; Shahidullah, M; Sk, Dey; Islam, MR; Islam, MF; Alam, MN (Bangladesh Journal of Neuroscience, 2016)
Background: Diagnosis of epilepsy is based mainly on clinical history and examination. EEG constitutes the single most valuable laboratory test in the evaluation of patients with epilepsy. Objective: The objective of the present study was to find out the frequency of EEG abnormality among different types of clinically diagnosed epileptic patients. Methods: This cross-sectional study was carried out in the Department of Neurology, Bangabandhu Sheikh Mujib Medical University, Dhaka. A total of 152 epileptic patients attended in the Epilepsy Clinic, General OPD and EEG room of the Department of Neurology were enrolled for this study. Information on socio-demographic and seizure characteristics was obtained. The records from patients were obtained using the standard data collection form. Result: Out of 152 epileptic patients male were 62.5% and female were 37.5%, mean age was 20.69 ± 11.83 years. Abnormal EEG was found in 81 (53.3%) patients. Most of the patients 64 (79.0%) had generalized epileptic discharge and 17 (21.0%) had focal epileptic discharge. Out of 81 patients with abnormal EEG wave, 31 (38.3%) patients had spike and wave, 26 (32.1%) patients had sharp wave and 24 (29.6%) patients had multiple types of EEG wave. Conclusion: The EEG is an important tool for diagnosing an epilepsy syndrome, knowledge of which aids in planning treatment and determining prognosis. Bangladesh Journal of Neuroscience 2016; Vol. 32 (2): 63-67